Patient experiences of co-designed rehabilitation interventions: protocol for a rapid review. Issue 1 (31st January 2022) - McKercher, Jonathan P; Slade, Susan C; Jazayeri, Jalal; Hodge, Anita; Knight, Matthew; Green, Janet; Woods, Jeffrey; Morris, Meg E
Abstract : Introduction: Patient-centred care can be facilitated by co-design, which refers to collaboration between healthcare professionals and consumers in producing and implementing healthcare. Systematic reviews on co-design have mainly focused on the effectiveness of co-produced healthcare interventions. Less attention has been directed towards the experiences of patients in co-designed interventions. This rapid review aims to explore patient experiences of co-designed rehabilitation interventions and inform rehabilitation decision-making. Methods and analysis: A rapid review will expedite timely information on co-design experiences for stakeholders. Four electronic databases, including Cochrane CENTRAL, MEDLINE, Embase and CINAHL, will be searched for papers published from 1 January 2000 to 1 January 2022. The Cochrane Risk of Bias tool will be used for randomised trials. Critical appraisal checklists from The Joanna Briggs Institute shall evaluate the risk of bias of non-randomised trials and qualitative studies. A narrative synthesis will be provided for the quantitative studies. Thematic synthesis will be conducted on qualitative findings. The overall strength of the evidence will be measured using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework for quantitative investigations and the GRADE-Confidence in Evidence from Reviews of Qualitative Research for qualitative studies. The results will be presented using narrative summaries, identified themes, summary tables, flow charts and quantitative statistical analyses. Ethics and dissemination: Ethics approval is not required for the review. The protocol and rapid review will be submitted to an online, open access and peer-reviewed journal for publication. The review findings will be rapidly translated to consumers, clinicians, healthcare leaders, organisations, researchers and policy makers via publications, evidence summaries, conferences, workshops, websites, social media and online events. PROSPERO registration number: CRD42021264547.